GATE/GEANT4 simulation of radiation risk induced cancer from mammographic screening. (April 2022) - Fathi, I.; Mkimel, M.; El baydaoui, R.; El rhazouani, O.; Mesradi, M.R.
Abstract: The main objective of the paper is to estimate organ risk of radiation-induced cancer using Monte Carlo simulation Gate/Geant4 applying the Moroccan breast screening guidelines using digital mammography (DM) technique taken into consideration two views (cranio-caudal (CC) and medio-lateral oblique (MLO)), considering the age range of 45–60 years. We apply a new approach consisting of the use of a female voxel phantom EVA and FASH 3 computational phantoms merged with three-layer heterogeneous mammographic phantoms to estimate the incidence risks of cancer on a particular organ and the calculation of the total effective risk of radiation-induced cancer. The effective risk (ER) discrepancy between standing posture phantom FASH 3 and supine posture EVA phantom for organs were: 29.9% (breast examined), 54.83% (thyroid), and 10.97% (total effective risk). These results show a posture sensitivity in terms of organ dose calculation. To investigate the impact of glandular distribution on the ER, each layer of the breast was set to a glandular fraction of 25%, 50%, or 75% to simulate a glandular heterogeneous distribution of uniform, concentrated, superior, and inferior glandular distributions. The heterogeneous distribution shows lower values of the total effective risk of radiation-induced cancer of those of uniform one. This finding shows that the total effective risk for radiation-induced cancer using voxel phantom and heterogeneous breast distribution should be considered in clinical practice to provide DRL in conventional breast dosimetry. Highlights: Estimation of risk of radiation-induced injury for digital breast mammography. Organ dose for FASH 3 and Eva phantom present a difference above 60%. Contralateral breast and lung were estimated to have a considerable effective risk. Effective risk is about 25.5% lower when a heterogeneous breast is considered.